2011
DOI: 10.1007/s10856-011-4352-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanometer scale particulate fillers on some properties of microfilled composite resin

Abstract: The aim of this study was to evaluate the effect of different weight fractions of nanometer sized particulate filler on properties of microfilled composite resin. Composite resin was prepared by mixing 33 wt% of resin matrix to the 67 wt% of silane treated microfine silica particulate fillers with various fractions of nanometer sized fillers (0, 10, 15, 20, 30 wt%) using a high speed mixing machine. Test specimens made of the composites were tested with a three-point bending test with a speed of 1.0 mm/min unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
2
29
1
1
Order By: Relevance
“…65 Moreover, Garoushi et al incorporated SiO 2 (20 nm) into micro-filled composite resin with loadings of 10, 15, 20 and 30 wt%. 66 The results of these four studies showed that neat resins have higher flexural strength than nano-composites. Table 4 shows the negative effects of nanoparticles on the flexural strength of dental composites.…”
Section: 54mentioning
confidence: 97%
See 1 more Smart Citation
“…65 Moreover, Garoushi et al incorporated SiO 2 (20 nm) into micro-filled composite resin with loadings of 10, 15, 20 and 30 wt%. 66 The results of these four studies showed that neat resins have higher flexural strength than nano-composites. Table 4 shows the negative effects of nanoparticles on the flexural strength of dental composites.…”
Section: 54mentioning
confidence: 97%
“…81,82 The surface area for the interaction between nanofillers and matrix decreases and fractures in the agglomerate sites are initiated. 66,83 4. Decreased cross-section of the load-bearing matrix.…”
Section: 6263mentioning
confidence: 99%
“…Volumetric polymerization shrinkage of dental resin was measured according to the method reported previously [21]. The specimen's densities (n = 5 per group) were measured to determine polymerization shrinkage using Archimedes' principle with a commercial Density Determination Kit of the analytical balance Mettler Toledo X (Mettler Instrument Co., Highstone, NJ, USA).…”
Section: Polymerization Shrinkagementioning
confidence: 99%
“…Clearly, factors required for high bond strengths between fiber and composite have been thoroughly investigated. In general, the mechanical properties of polymerized composite resin materials are related to monomer type (18) and filler type (19).…”
Section: Introductionmentioning
confidence: 99%